Synthesis and Optical Characterization of Mg1-xNixO Nanostructures. (20th November 2012) - Budiredla, Nageswararao; Kumar, Ashok; Thota, Subhash; Kumar, Jitendra
Abstract : An attempt has been made here to synthesize Mg 1 - x Ni x O   ( 0.0 1 ≤ x ≤ 0.10 ) nano-powders via sol-gel process. These powders are shown to possess an f.c.c. (NaCl-type) structure with a typical lattice parameter of 4.228 ( 2 )  Å for " x " = 0.01 when decomposition of dried oxalate gel product is carried out at 600°C for 2 h in air. Moreover, they exhibit (i) clusters/agglomerates of nanosize particles and (ii) high BET specific surface area (123.0–135.5 m 2 /g). Also, the infrared absorption spectra reveal their strong affinity to water. The UV-Vis absorption peaks appearing at ~202 nm, 296 nm, and 379 nm are associated with oxygen defect centres and correspond to the electronic transitions (i) A 1 1 g → T 1 1 u (1 s → 2 p x, 2 p y, or 2 p z ), (ii) A 1 1 g → E 1 (1 s → 2 p x, or 2 p y ) and (iii) A 1 1 g → A 1 1 g (1 s → 2 p z ), respectively. The incorporation of Ni 2+ ions causes some modifications in the energy levels and the optical absorbance characteristics. The suppression of a strong broad emission peak at 440 nm and improvement of a weak band at ~ 400 nm in the photoluminescence (PL) spectrum arise due to decrease in population density of F 2 2 + centres (or F + dimmers) and emergence of additional F + centres, respectively with increase in nickel content.